La articulación de intereses de los Moyāhedīn-e Jalq-e Iran: de la Revolución islámica al Movimiento Verde - Garduño, Moisés (El Colegio de México, 2016)
This paper defends the hypothesis that the political survival of the Mojahedin-e Khalq-e Iran Organization (The Fighters of the People of Iran) is dependent upon the recognition of this group’s joint interests with the political competitors of the Islamic Republic of Iran and not due to the effectivenessof any discursive or political project as these might relate to the Iranian society at large.The Mojahedin-e Khalq-e Iran Organization participated in the Islamic Revolution of 1979 alongside Khomeini and many other political factions against the police, military and intelligence forces of the Pahlavi monarchy. However, after the Revolution, a clash of interests between the organiza-tion and the new elite led by Ayatollah Khomeini surged to the fore and caused an atmosphere of tension and distrust that lead to a new armed confrontation between these organizations. This war led the Mojahedin-e Khalq and their leaders, Massoud and Maryam Rayavi, to establish an alliance with Saddam Hussein in Iraq who provided them with weapons, money and military training in order to attack the nascent Islamic Republic of Iran, killing several politicians and key figures of the Iranian politics as well as thousands of civilians.The strategic position that the Mojahedin-e Khalq had in Iraq was main-tained until the last day of the existence of the Baathist regime when, after the US invasion in 2003, Saddam Hussein was overthrown and sentenced to death. This left the organization with the following dilemma: to disappear forever or to join the Western invader whom they had criticized during the initial years of political activism. The decision taken was to opt for thelatter in order to go ahead with their quest for power in Iran and their own political survival.While this group is the strongest and well-organized opposition group against the Islamic Republic of Iran today, the Mojahedin survive because of the historical way in which they have sold their political, military and intelligence services to countries like Iraq, the United States and Israel, in order to continue working as an opposition political organization with funding from its allies and other resources obtained by the manipulation of its social base. To this population the Mojahedin promises the establishmentof a “Democratic Islamic Republic of Iran”, a model in which they call for the defense of democracy, the secular state, human rights and the observance of the free market ideology. All of these being principles contrary to the Islamo-Marxist ideas they espoused during their first twenty years of political activism.This text analyzes the period from 1980 to the present (2015). This allowsus to consider the consequences of the direct armed confrontation andmutual demonization carried out between the Mojahedin-e Khalq-e Iranand the political elite of the Islamic Republic of Iran. These are conflicts af-fecting not only the internal policy of the Iranian regime but also its internationalrelations and foreign policy in sensitive issues such as the promotion of the Iranian revolutionary model in the Middle East, the Iranian nuclear program and the issues related to the Green Movement.